Environmental footprint of in-center hemodialysis in Türkiye: A national, scenario-based analysis of water, energy, and waste - Berrak Itır Aylı; Mehmet Emin Demir; Arzu Akgül; Hatice Şahin (PLoS ONE, 2026)
Background Hemodialysis (HD) is a life-sustaining but resource-intensive therapy, consuming large volumes of water and electricity and generating substantial waste. This hybrid modeling study quantified the environmental footprint of in-center HD in Türkiye using national registry data, published parameters, and measured facility-level data from two Turkish dialysis centers. Methods A hybrid modeling approach combined published per-session resource parameters with measured facility-level data from two Turkish hemodialysis centers (4,000 sessions/month combined). Literature-derived parameters (493 L water/session at 42% RO recovery, 6.2–19.6 kWh electricity/session, 1.5–8.0 kg waste/session) were scaled nationally for 2023 (9.27 million sessions). Measured Turkish data (390 L water, 10.8 kWh electricity, 1.19 kg hazardous waste per session) provided empirical calibration. GHG emissions were calculated using Türkiye-specific (0.494 kg CO 2 e/kWh for electricity) and international conversion factors. Results Using literature parameters, annual national estimates include 4.57 million m³ water, 57.5–181.8 GWh electricity, and 13.9–74.2 kt waste, with total GHG emissions ranging from 45.3 to 171.1 kt CO 2 e/year. Measured Turkish facility data yielded lower per-session water consumption (~390 L vs. 493 L, a 21% reduction) and hazardous waste generation (1.19 vs. 1.5 kg/session under good segregation), while electricity consumption (mean 10.8 kWh/session) aligned with the moderate literature scenario. Electricity was the dominant emission source (63–72%), followed by waste incineration (up to 47% with poor segregation). Conclusion In-center HD in Türkiye imposes a substantial yet modifiable environmental burden. Measured Turkish facility data demonstrated that actual water consumption is meaningfully lower than international estimates, highlighting the importance of locally validated parameters. Waste segregation and electricity decarbonization represent the highest-impact intervention points for reducing the sector’s carbon footprint.